Pharmacological and Pathological Relevance of S100 Proteins in Neurological Disorders - Goswami, Deepali; Anuradha, Urati; Angati, Anok; Kumari, Nisha; Singh, Rakesh K. (CNS & Neurological Disorders - Drug Targets, 2023)
The S100 protein is one of the calcium-binding proteins associated with Alzheimer's disease, Parkinson's disease, and amyotrophic lateral sclerosis. S100 proteins are expressed in the central nervous system by oligodendrocytes, astrocytes and neurons during both normal and disease conditions. Although amyloid-beta aggregation and hyperphosphorylated tau plaques are the main pathological hallmarks of Alzheimer's disease, the S100 protein family is closely associated with neuroinflammation in several neurodegenerative disorders, such as Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis in addition to various types of cancer and other brain diseases. This review aims to present the key role of S100 proteins and their different relevant isoforms, along with the various approaches used for the regulation of these proteins in several neurodegenerative disorders.
Keywords: brain biomarker